Thermodynamics: An Interactive Approach, Global Edition - Bhattacharjee, Subrata (Pearson International Content, 2016)
For the thermodynamics course in the Mechanical & Aerospace Engineering department   Thermodynamics: An Interactive Approach employs a layered approach that introduces the important concepts of mass, energy, and entropy early, and progressively refines them throughout the text. To create a rich learning experience for today’s thermodynamics student, this book melds traditional content with the web-based resources and learning tools of TEST: The Expert System for Thermodynamics (www.pearsonhighered.com/bhattacharjee)–an interactive platform that offers smart thermodynamic tables for property evaluation and analysis tools for mass, energy, entropy, and exergy analysis of open and closed systems.     MasteringEngineering not included. Students, if MasteringEngineering is a recommended/mandatory component of the course, please ask your instructor for the correct ISBN and course ID. MasteringEngineering should only be purchased when required by an instructor. Instructors, contact your Pearson representative for more information. MasteringEngineering for Thermodynamics is a total learning package. This innovative online program emulates the instructor’s office—hour environment, guiding students through engineering concepts from Thermodynamics with self-paced individualized coaching.   Teaching and Learning Experience To provide a better teaching and learning experience, for both instructors and students, this program will: Personalize Learning with Individualized Coaching: MasteringEngineering emulates the instructor’s office-hour environment using self-paced individualized coaching. Introduce Fundamental Theories Early: A layered approach introduces important concepts early, and progressively refines them in subsequent chapters to lay a foundation for true understanding. Engage Students with Interactive Content: To create a rich learning experience for today’s thermodynamics student, this book melds traditional content with web-based resources and learning tools.